2004
DOI: 10.1152/ajpregu.00409.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of exercise and diuretic on left ventricular geometry, mass, and insulin resistance in older hypertensive adults

Abstract: . Comparison of effects of exercise and diuretic on left ventricular geometry, mass, and insulin resistance in older hypertensive adults. Am J Physiol Regul Integr Comp Physiol 287: R360 -R368, 2004. First published April 29, 2004; 10.1152/ajpregu.00409.2003.-To compare the effects of exercise training and hydrochlorothiazide on left ventricular (LV) geometry and mass, blood pressure (BP), and hyperinsulinemia in older hypertensive adults, we studied 28 patients randomized either to a group (age 66.4 Ϯ 1.3 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…Along this line of thought, low-intensity exercise delays the onset of heart failure in aging SHR [24,25]. Clinical studies have also shown that endurance exercise training is accompanied by a reduction in left ventricle hypertrophy in elderly hypertensive patients receiving antihypertensive treatment (or not) [10,14,26]. This reduction was similar to that observed with a diuretic treatment [14].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Along this line of thought, low-intensity exercise delays the onset of heart failure in aging SHR [24,25]. Clinical studies have also shown that endurance exercise training is accompanied by a reduction in left ventricle hypertrophy in elderly hypertensive patients receiving antihypertensive treatment (or not) [10,14,26]. This reduction was similar to that observed with a diuretic treatment [14].…”
Section: Discussionmentioning
confidence: 67%
“…Experimental and clinical studies have demonstrated that acute and chronic exercise (static, aerobic endurance or resistance) have beneficial effects on BP levels [8][9][10][11][12]. This benefit is accompanied by a regression of cardiovascular adjustments that occurs with hypertension [9,10,[13][14][15]. However, most of these studies have been performed in young or middle-aged individuals or animals and have evaluated the effects of short-term and long-term exercise training in the progression of hypertension; few studies have explored whether or not this benefit can be extended to elderly hypertensive animals.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Rinder et al. (2004) demonstrated a significant correlation between reductions in systolic blood pressure and reduced relative wall thickness and reported an increase in stroke volume, cardiac output, and LV ejection fraction in their exercise training group. Other lifestyle interventions, such as low sodium diets have demonstrated significantly improved LV diastolic function with significantly reduced ABP in hypertensive heart failure patients (Hummel et al.…”
Section: Discussionmentioning
confidence: 99%
“…These favorable LV remodeling responses to acute IE are similar to those reported in patients with hypertension following a program of aerobic exercise training or prescribed diuretics (Rinder et al. 2004). A single IE training session was associated with improved global longitudinal, circumferential strain and strain rate and apical radial strain as well as increased LV twist and untwist.…”
Section: Discussionmentioning
confidence: 99%
“…e effects of exercise training on cardiac remodeling in hypertensive human subjects have been reviewed elsewhere [63] and have shown equivocal results with some studies showing no change in le ventricular mass [64][65][66][67][68][69], a decrease in le ventricular mass/le ventricular mass index [64,[70][71][72][73][74], and an increase in le ventricular mass/le ventricular mass index [5,66]. e majority of these studies showed that systolic and diastolic blood pressure was reduced following exercise, and imaging was most oen measured with M-mode and 2D guided echocardiography.…”
Section: Cardiac Remodelingmentioning
confidence: 99%